2009
DOI: 10.1111/j.1600-051x.2009.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of statin medication on the periodontium

Abstract: Statin medication appears to have an effect on the periodontium that is dependent on the inflammatory condition of the periodontium. More evidence is needed to achieve a comprehensive understanding of the effects of statins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 23 publications
0
52
1
Order By: Relevance
“…Regarding the systemic consumption of statins by patients at risk for CVD, recent retrospective studies 35,36 have supported a positive role of statins for the periodontium. The findings of Saxlin et al 37 also lend credence to this assumption.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Regarding the systemic consumption of statins by patients at risk for CVD, recent retrospective studies 35,36 have supported a positive role of statins for the periodontium. The findings of Saxlin et al 37 also lend credence to this assumption.…”
mentioning
confidence: 80%
“…Another retrospective study by Lindy et al 36 concluded that statin medication use was associated significantly with fewer signs of periodontal inflammatory injury. Saxlin et al 37 concluded that the effect of statins on the periodontium may depend on the inflammatory status of periodontium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Saxlin et al. (41) reported that among subjects with no gingival bleeding, statin medication was associated with an increased likelihood of having teeth with deepened periodontal pockets. Two recently completed prospective studies support the role of statins as an adjunctive therapeutic in the treatment of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that patients on statin medication exhibited reduced periodontal injury as compared to subjects without the drugs [9]. Statin medication may have some beneficial effects when subjects have dental plaque or signs of periodontitis as gingival bleeding [10]. Thus, the question arises whether statins may have an influence on periodontal parameters by affecting either the inflammation or the association between the disease and the cholesterol concentration or both.…”
Section: Introductionmentioning
confidence: 99%